Deconstructing Hijabs in Sabyn Javeri’s Hijabistan - Shenaz Parween (UIN Syarif Hidayatullah Jakarta, 2023)
In the contemporary world of racism and Islamophobia, the Hijab is just the tip of an iceberg, while its meanings are far deeper and more complicated. These heterogeneous meanings of the Hijab and its wearer in the outside world are well handled by Sabyn Javeri, a Pakistani award-winning author and Professor, in her short-story collection called Hijabistan. Comprising 16 politically provocative short stories based on the metaphorical interpretation of the veil in the lives of Muslim women, Javeri challenges the single one-dimensional narratives of hijabi identity by presenting the real usage of Hijab in the right and wrong way within the current society. In each story, the Hijab, takes on a new role; for some it becomes a weapon to satisfy one’s urges, while for others it functions as a source of patriarchal oppression or a symbol of segregation from mainstream society. There are also a few who wear the Hijab as a badge of honor, while others do not see it as a barrier within their active sexual life. The paper focuses on these multi-dimensional meanings of the Hijab while critically analyzing how the characters achieved their goals while wearing the veil and how some are seeking their identity.